2018
DOI: 10.1016/j.dci.2018.02.019
|View full text |Cite
|
Sign up to set email alerts
|

Beta-glucan enhances the response to SVCV infection in zebrafish

Abstract: The antiviral effects of beta-glucan, an immunostimulatory agent were studied in zebrafish both in vitro and in vivo. Here we show that zebrafish ZF4 cells as well as whole fish primed with yeast β-glucan zymosan exhibited increased cytokine expression and elevated response to spring viremia of carp virus (SVCV) infection. In vitro, previous treatment of β-glucan enhanced ZF4 cell viability against SVCV infection which is associated to the activation of interferon signaling pathway and inflammatory cytokines g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
37
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(39 citation statements)
references
References 39 publications
1
37
0
1
Order By: Relevance
“…injection of β-glucans in trout revealed that beyond 36 days poststimulation, a higher mortality rate occurred in pre-immunized individuals ( 28 ). The genes encoding proinflammatory cytokines, such as TNF-α, IL-1β, and IL-6, which are usually found to be upregulated during cell training ( 15 , 32 , 53 ) were not differentially modulated in our microarray results. These findings, together with the absence of protection against SVCV, led us to consider that in this work, we are describing long-term mechanisms that could persist beyond the end of training immunity.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…injection of β-glucans in trout revealed that beyond 36 days poststimulation, a higher mortality rate occurred in pre-immunized individuals ( 28 ). The genes encoding proinflammatory cytokines, such as TNF-α, IL-1β, and IL-6, which are usually found to be upregulated during cell training ( 15 , 32 , 53 ) were not differentially modulated in our microarray results. These findings, together with the absence of protection against SVCV, led us to consider that in this work, we are describing long-term mechanisms that could persist beyond the end of training immunity.…”
Section: Discussionmentioning
confidence: 55%
“…The trained immunity induced by β-glucans seems to be limited to a period of approximately 20 days. This effect was observed after in vitro stimulation of murine spleen-derived monocytes with this substance ( 53 ) and after in vivo stimulation in zebrafish ( 32 ). Moreover, a work based on long-term protection against the virus IHNV after an i.p.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Unlike several previously published in vitro trials in carp (Biswas et al ., ; Pietretti et al ., ; Kareem et al ., ), here β‐glucan significantly reduced overall expression of il‐1β in the gut. In contrast to in vitro trials, the effect of β‐glucan upon inflammatory cytokine gene expression in vivo has produced inconsistent results (Djordjevic et al ., ; Falco et al ., ; Medina‐Gali et al ., ). In our study however, there was no indication that the downregulation of il‐1β expression as measured by rt‐qPCR had a detrimental effect upon the overall health of the fish.…”
Section: Discussionmentioning
confidence: 97%
“…Nowadays, β-glucans have attracted considerable attention due to their anti-infective, antiviral, antitumor, and immunomodulatory activities as well as wound healing properties [2][3][4][5][6][7]. As for their antiviral effect, β-glucans have shown excellent activity against a broad spectrum of plant, animal, and human viruses, such as the infectious haematopoietic necrosis virus [8], spring viremia of carp virus [9], dengue virus [10], herpes simplex virus type 1 (HSV-1) [11], human immunodeficiency virus 1 [12], influenza virus [13,14], and tobacco mosaic virus [15]. Despite in vitro and in vivo evidence of the antiviral effect of β-glucans, to date, only a few human and animal clinical studies have been conducted utilizing β-glucans in treatment or prevention of viral infections [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%